Bibliometric Analysis of the Trends of Publications on Poverty Research in Tanzania from 1961 to 2016 - Msoffe, Grace E. P.; Sife, Alfred S. (University of Dar es Salaam Library Journal, 2021)
Poverty research is essential in understanding the evolution of poverty, poverty trends and dynamics, policy formulation, prioritising policy interventions and informed decision making. To date, a bibliometric analysis of poverty research in Tanzania does not exist in the literature. Therefore, this bibliometric study was conducted to assess the research trends on poverty in Tanzania between 1961 and 2016. Data were collected through Harzing's Publish or Perish tool, which uses Google scholar to retrieve data from the web. A total of 825 publications were retrieved, with an average of 14.7 publications per year. As the growth rate of publications increased, the corresponding doubling time decreased. Journal articles were the dominant (23.9%) type of publication. The degree of collaboration among researchers was low, with the majority (52.8%) of publications having one author. The citation analysis reveals that over a third (35.76%) of publications were not cited. Subject categories related to poverty that had a relatively higher number of publications were governance (10.2%), agriculture (9%) and community (8.6%). Generally, the study findings provide valuable information on the characteristics of poverty research in Tanzania, which can reference future research.